EFEKTIFITAS PELVIC ROCKING TERHADAP KELANGSUNGAN PERSALINAN PADA PRIMIGRAVIDA FASE AKTIF DI WILAYAH KERJA PUSKESMAS BISSAPPU - Rusli Taher; Muliyana; Nurhikmah; Reskiawati Azis (Stikes Graha Edukasi Makassar, 2022)
Background : Pelvic Rocking with Birthing Ball is to increase the size of the pelvic cavity by shaking the pelvis with the ball and slowly swinging the hips back and forth, right, left, and circular. Pelvic rocking can help the mother in an upright position, staying upright during labor will allow the uterus to work as efficiently as possible by making the pelvic area wider and open. Design: The study was conducted in November 2021 in the Working Area of ??the Bissappu Health Center. This type of research is the Quasy Experiment method with the Two Group Posttest approach. The sample in this study were 30 mothers in labor, then divided into 15 treatment groups and 15 control groups using purposive sampling technique. Results: The results showed that of the 30 people who were used as samples, 15 people (50.0%) did pelvic rocking and 15 people (50.0%) did not do pelvic rocking and those who experienced continuation of the first stage of labor active fast as many as 17 people (56.7%) and slow as many as 13 people (43.3%). Conclusion: There is an effectiveness of pelvic rocking on the continuity of the first active phase of labor in primigravidas with a value of ? = 0.000. Suggestion: It is hoped that the midwife on duty will increase her attention in providing information about pelvic rocking